COUNTER PRESSURE UNTUK MENGURANGI RASA NYERI PERSALINAN (EVIDENCE BASED CASE REPORT): Indonesia (Politeknik Kesehatan Kemenkes Bandung, 2022)
Due to the uterus' natural activity, almost all pregnant women who undergo labor feel discomfort. As lessen discomfort, pain management is required. The control pressure technique is one of the non-drug ways to lessen discomfort. This case study uses data to support its conclusion that the counter pressure technique is beneficial in lowering labor discomfort. This evidence-based case report strategy uses journal database searches. Using the search terms